Comparison between observations and gridded data sets over complex terrain in the Chilean Andes: Precipitation and temperature. (3rd March 2020) - Schumacher, Vanúcia; Justino, Flávio; Fernández, Alfonso; Meseguer‐Ruiz, Oliver; Sarricolea, Pablo; Comin, Alcimoni; Peroni Venancio, Luan; Althoff, Daniel
Abstract: This study describes the performance of five gridded data sets in reproducing precipitation and/or temperature over the complex terrain in the high Chilean Andes. The relationship of instrumental observations and the gridded data sets with climate modes of variability and the trends of indices of climate extremes are also explored between the period 1980–2015. The mismatches between gridded data sets are larger in northern and southern regions in relation to precipitation, while for temperature, disagreement is higher in central region. However, better results are delivered by the Climatic Research Unit and Global Precipitation Climatology Centre followed by Re‐Analysis Interim Project. The El Niño Southern Oscillation and Pacific Decadal Oscillation indices are well correlated with precipitation in North and South Chile. Additional, trend analyses reveal a significant downward (upward) tendency for precipitation (temperature), especially in central region, delivered by observed and the majority of gridded data sets. Furthermore, the consecutive number of dry days is increasing in all regions at the annual scale. This study allows a better understanding of the capacity of global data sets and thus contributes to further climate research within this Andean region. Abstract : This study describes the performance of five gridded data sets in reproducing precipitation and/or temperature over the complex terrain in the high Chilean Andes. The relationship of instrumental observations and the gridded data sets with climate modes of variability and the trends of indices of climate extremes are also explored between the period 1980–2015. Regionally, disagreement is larger over Northern and Southern Chile for precipitation and over Central Chile for temperature. A trend analyses reveal a significant downward for precipitation and upward for temperature, especially in central region, delivered by observed and the majority of gridded data sets.